2020
DOI: 10.1128/msystems.00515-20
|View full text |Cite|
|
Sign up to set email alerts
|

Physical Activity Shapes the Intestinal Microbiome and Immunity of Healthy Mice but Has No Protective Effects against Colitis in MUC2 −/− Mice

Abstract: The interactions among humans, their environment, and the trillions of microbes residing within the human intestinal tract form a tripartite relationship that is fundamental to the overall health of the host. Disruptions in the delicate balance between the intestinal microbiota and host immunity are implicated in various chronic diseases, including inflammatory bowel disease (IBD). There is no known cure for IBD; therefore, novel therapeutics targeting prevention and symptom management are of great interest. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 99 publications
(119 reference statements)
4
9
0
Order By: Relevance
“…Furthermore, the reduced running distance was paralleled by a decrease in the muscle strength assessed by the grip test in these mice compared with healthy mice. The running distance on the SW of healthy mice well corresponded with the similar range, 1.3 and 1.1 km/day, reported before in mice without colitis [38]. The access of mice to SW in all groups led to a reduction of their body weights, especially notable in those fed with diet-induced obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the reduced running distance was paralleled by a decrease in the muscle strength assessed by the grip test in these mice compared with healthy mice. The running distance on the SW of healthy mice well corresponded with the similar range, 1.3 and 1.1 km/day, reported before in mice without colitis [38]. The access of mice to SW in all groups led to a reduction of their body weights, especially notable in those fed with diet-induced obesity.…”
Section: Discussionsupporting
confidence: 86%
“…By analyzing colonic tissue, we revealed a significant decrease in Ifng, ll10, Ccl2, S100b, and Iba1 (Figure 3B). Down-regulation of Ifng was also detected in colonic tissue of 2-3 months old mice after 6 weeks of VWR [51]. These mice were also characterized by a decrease in Tnf, which was not significantly changed in our aged mice, and an increase in the protective Il10 [51], which we found downregulated in the aged colon after running (Figure 3B).…”
Section: Gene Expression Changes During Aging Following Running and S...supporting
confidence: 48%
“…Down-regulation of Ifng was also detected in colonic tissue of 2-3 months old mice after 6 weeks of VWR [51]. These mice were also characterized by a decrease in Tnf, which was not significantly changed in our aged mice, and an increase in the protective Il10 [51], which we found downregulated in the aged colon after running (Figure 3B). Mice with induced colitis were subjected to forced moderate exercise, which led to an increase in cytokines such as Tnf, Il1b, and Il10 in the colon and exacerbated colitis symptoms, whereas 30 days of VWR attenuated colitis in these mice and was associated with a decrease in Tnf [52].…”
Section: Gene Expression Changes During Aging Following Running and S...supporting
confidence: 48%
“…The concentration of lactate in human feces is relatively low (< 5 mM) because of the presence of bacteria that convert lactate to butyrate (Duncan et al, 2004). More recently, we have learned that physical exercise and physical fitness encourage diversity of species including those that act to convert lactate to butyrate (Estaki et al, 2016;Estaki et al, 2020). Recently also, the presence of "performance-enhancing" gut microbes, members of the genus Veillonella, in the stools of marathon runners (Scheiman et al, 2019) have been found.…”
Section: Can the Splanchnic Bed Be A Source Of Lactate?mentioning
confidence: 99%